RISK ASSESSMENT OF LOGISTICS PROJECT IMPLEMENTATION IN THE INITIAL STAGE - A. I. Kuzmich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The problem of risk assessment in the logistics projects implementation is studied. The solution for BOL-step in the methodology CL2M is presented. As a result, a theoretical basis for automating the risk assessment of the project in the initial stage, which reduces the likelihood of errors in other stages, is offered.